2023
DOI: 10.1021/acsomega.2c08027
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Blending of Recycled Poly(ethylene terephthalate)/Recycled Polypropylene: Kinetics Modeling of Non-Isothermal Crystallization

Abstract: Plastics were developed to change our world for the better. However, plastic pollution has become a serious global environmental crisis. Thermoplastic polyesters and polyolefins are among the most abundant plastic waste. This work presents an in-depth non-isothermal crystallization kinetics analysis of recycled post-consumer poly(ethylene terephthalate) (rPET) and recycled polypropylene (rPP) blends prepared through reactive compounding. The effect of pyromellitic dianhydride (PMDA) on crystallization kinetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
2
3
0
Order By: Relevance
“…At a given cooling rate, the CRC results indicated an increase in crystallization with increased OMCC amount. Additionally, it was found that 3#OMCC had the fastest crystallization rate, which is well consistent with the our above and reported results …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…At a given cooling rate, the CRC results indicated an increase in crystallization with increased OMCC amount. Additionally, it was found that 3#OMCC had the fastest crystallization rate, which is well consistent with the our above and reported results …”
Section: Resultssupporting
confidence: 93%
“…The crystallization properties of PBAT are mainly influenced in two ways: (1) one is introduction of nucleating agents . Inorganic and organic nucleating agents have been used to enhance the polymer properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, at different temperatures, the curve fitted by the Ozawa equation has a large deviation, and the comparison between S0 and the parameters of S1.5 and S3.0 regarding the Ozawa equation has no reference value. Therefore, the Ozawa method does not apply to polymers with different crystallization processes [47], which is consistent with the results of previous studies [48].…”
Section: Ozawa Methodssupporting
confidence: 90%
“…According to previous studies, an increased content of rPP reduces the crystallinity of the rPET phase in blends, which indicates that invasive polymer influence the crystallization behavior of the virgin polymer. 47 In light of aforesaid result, it is indicates that more non-crystalline regions were formed by irregularly arranged chains in rHDPE compared to vHDPE films. Moreover, the addition of 25 wt%, 50 wt%, and 75 wt% V1 into rHDPE films of R2 results in the increasing of crystallinity by almost 2.8%, 5.9%, and 9.4%, respectively.…”
Section: Thermal Properties and Thermal Stability Of Rhdpe And Vhdpementioning
confidence: 85%